PEMBERDAYAAN EKONOMI KREATIF MASYARAKAT DALAM ANEKA OLAHAN PEPAYA MELALUI PERAN KKN PPM DI DESA GUMUK KECAMATAN LICIN KABUPATEN BANYUWANGI - Anis Fauzi; Imam Wahyono; Firma Yudha (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2020)
Rationally, the combination of businesses in agriculture and animal husbandry is mutually supportive. This means that in addition to the main harvest in the form of cropping, by-products are also obtained, namely abundant forage for livestock. On the other hand, from livestock farming, it primarily generates economic benefits from the sale of livestock, and in the secondary produces manure which is essential for increasing agricultural production. The KKN-PPM activity is intended to provide a real touch of empowering agricultural sector businesses, where agricultural products will be innovated into processed products. To increase agricultural productivity, skills and other innovations are needed. But so far, farmers in Gumuk Banyuwangi Village are still selling their crops in the form of fruit. Knowledge about product innovation is still minimal. so that during the high harvest, prices plummeted, and some were even wasted. Even though at the KKN-PPM activity location, there are so many materials available to support the manufacture of papaya preparations, where then the papaya will be innovated into processed Papaya Candy and Papaya Shredded.